A method for preparing lithium iron manganese phosphate positive electrode material
By using silane coupling agent and sucrose on lithium manganese phosphate material to form a uniform and complete cladding layer, and then covering the carbon source, the problem of poor conductivity of lithium manganese phosphate material is solved, and more efficient carbon cladding effect is achieved and battery performance is improved.
Patent Information
- Application Number
- CN202211546008.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-05
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2042-12-05
AI Technical Summary
The poor conductivity of lithium manganese iron phosphate material limits its application in lithium-ion batteries, and the existing carbon coating method is costly and complex.
A silane coupling agent is used as the first layer of coating material, lithium manganese iron phosphate is coated, and a carbon source is coated thereon, and hydrogen bonds are formed with sucrose and silane coupling agent to improve the uniformity and integrity of the coating layer.
It improves the uniformity and integrity of carbon coating, reduces the amount of carbon source added, and improves the conductivity, capacity, rate performance and service life of the cathode material.
Smart Images

Figure CN115974032B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a lithium manganese iron phosphate positive electrode material. Background Art
[0002] As a secondary battery, lithium-ion battery has the advantages of high energy density, no memory effect, and long service life. It is a new type of green and environmentally friendly battery that occupies an important position in the fields of power and energy storage. Lithium-ion batteries with lithium iron phosphate as the positive electrode material can have the advantages of cost, safety and service life, but the energy density of lithium iron phosphate batteries is relatively low. In recent years, domestic and foreign scholars have conducted extensive research on lithium iron phosphate materials. Due to the high voltage platform of this material, it can effectively increase the energy density by 15%-20% compared with lithium iron phosphate. However, the poor conductivity of lithium iron phosphate materials limits its application.
[0003] At present, the industry mainly adopts nano-sizing, surface coating and element doping measures for the modification and optimization of lithium manganese iron phosphate. Among them, carbon coating is the lowest cost and most effective improvement method. Coating a carbon layer on the outside of the positive electrode material can enhance the conductivity between particles, reduce the polarization of the battery, and shorten the diffusion distance of lithium ions by inhibiting the growth of grains. In order to increase the coating effectiveness of carbon materials, several times the stoichiometric ratio of carbon sources are usually coated, but too high a coated carbon content will result in low gram capacity of the active material and poor processing performance. Therefore, many companies start from improving coating equipment and optimizing process routes, hoping to improve the effect of carbon coating, but this will undoubtedly increase production costs. Therefore, we need to develop a low-cost and simple process carbon coating method to solve the above problems. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings of the above-mentioned background technology and provide a method for preparing a lithium iron manganese phosphate positive electrode material. In order to improve the uniformity and integrity of the carbon coating, the method uses a silane coupling agent as the first layer of coating material to coat the lithium iron manganese phosphate, and uses a carbon source as the second layer of coating material to coat the silane coupling agent layer. The silane coupling agent serves as a binding layer between the lithium iron manganese phosphate and the carbon source, which can enhance the binding effect between the two. Then, sucrose is added. After the sucrose is dissolved in water, its hydroxyl group forms a hydrogen bond with the amino group of the silane coupling agent, which can enhance the binding effect between the two, so that the sucrose is evenly and completely coated with the silane coupling agent layer.
[0005] To achieve the purpose of the present invention, the method for preparing the lithium manganese iron phosphate positive electrode material of the present invention comprises the following steps:
[0006] (1) adding a lithium source, an iron source, a manganese source, and a phosphorus source into a ball mill containing ethanol and mixing by ball milling to obtain a mixture;
[0007] (2) drying the mixture obtained by mixing in step (1), placing it in a tube furnace, and calcining it in an inert atmosphere to obtain a lithium manganese iron phosphate sintered precursor;
[0008] (3) adding the lithium manganese iron phosphate sintering precursor and the silane coupling agent into a ball mill filled with deionized water and mixing them by ball milling;
[0009] (4) adding sucrose to the mixture obtained by mixing in step (3), and mixing by ball milling;
[0010] (5) drying the mixture obtained by mixing in step (4), placing it in a tube furnace, calcining it in an inert atmosphere, and finally sieving it to obtain a modified lithium manganese iron phosphate positive electrode material.
[0011] Furthermore, in some embodiments of the present invention, in step (1), the lithium iron manganese phosphate material LiFe x Mn 1-x PO 4 A lithium source, an iron source, a manganese source and a phosphorus source are added in a molar ratio, wherein the Mn / Fe element molar ratio = 1-x / x, 0.1≤x≤0.8.
[0012] Furthermore, in some embodiments of the present invention, the ball milling time in step (1) is 4-8 hours.
[0013] Furthermore, in some embodiments of the present invention, the calcination temperature in step (2) is set at 500-650°C.
[0014] Furthermore, in some embodiments of the present invention, the calcination time in step (2) is set at 2-10 hours.
[0015] Furthermore, in some embodiments of the present invention, the silane coupling agent is selected from one or more of 3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, and 3-aminopropyltrimethoxysilane. The silane coupling agent layer serves as a bonding layer between the lithium manganese iron phosphate and the carbon source, which can enhance the interaction between the lithium manganese iron phosphate and the carbon source and improve the uniformity and integrity of the carbon coating.
[0016] Furthermore, in some embodiments of the present invention, the amount of the silane coupling agent added is 1-10 wt %.
[0017] Furthermore, in some embodiments of the present invention, the ball milling time in step (3) is 2-6 hours.
[0018] Furthermore, in some embodiments of the present invention, the ball milling time in step (4) is 2-6 hours.
[0019] Furthermore, in some embodiments of the present invention, the amount of sucrose added in step (4) is 5-20 wt %.
[0020] Furthermore, in some embodiments of the present invention, the calcination temperature in step (5) is set at 650-800°C.
[0021] Furthermore, in some embodiments of the present invention, the calcination time in step (5) is set at 4-14 hours.
[0022] Compared with the prior art, the advantages of the present invention are as follows:
[0023] (1) After the silane coupling agent in the present invention is hydrolyzed in deionized water, the generated Si-O-bond can form a strong chemical bond with the lithium iron manganese phosphate crystal interface to increase the binding force between the two, forming a uniform and complete coating layer on the outside of the lithium iron manganese phosphate. Then, sucrose is added. After the sucrose is dissolved in water, its hydroxyl group will form a hydrogen bond with the amino group of the silane coupling agent, which can enhance the binding effect between the two, so that the sucrose can evenly and completely cover the silane coupling agent layer.
[0024] (2) The present invention coats a layer of silane coupling agent on the outer layer of lithium manganese iron phosphate to fix the lithium manganese iron phosphate and the carbon coating layer, thereby improving the uniformity and integrity of the carbon coating, reducing the amount of carbon source added, improving the processing performance of the positive electrode material slurry process, and increasing the gram capacity, rate performance and service life of lithium manganese iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of the modification of lithium manganese iron phosphate material of the present invention;
[0026] Figure 2 Schematic diagram of the mechanism of action of the silane coupling agent of the present invention, taking 3-aminopropyltriethoxysilane as an example;
[0027] Figure 3 This is the XRD diagram of the lithium manganese iron phosphate material obtained by the present invention;
[0028] Figure 4 This is a SEM image of the lithium manganese iron phosphate material obtained by the present invention;
[0029] Figure 5 0.2C charge-discharge curves of the lithium manganese iron phosphate materials obtained in Example 1 and Comparative Example 1 of the present invention;
[0030] Figure 6 It is a schematic diagram of the rate performance of the lithium manganese iron phosphate material obtained in Example 1 of the present invention and Comparative Example 1;
[0031] Figure 7 It is a schematic diagram of the 0.2C cycle performance of the lithium manganese iron phosphate material obtained in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be understood through the practice of the present invention. It should be understood that the following description is only used to explain the present invention and is not intended to limit the present invention.
[0033] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.
[0034] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.
[0035] When amount, concentration or other value or parameter is expressed as range, preferred range or a series of upper preferred value and lower preferred value limit range, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.
[0036] Singular forms include plural references unless the context clearly indicates otherwise. "Optional" or "either" means that the subsequently described event or incident may or may not occur, and that the description includes instances where the event occurs and instances where it does not.
[0037] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0038] In addition, the descriptions of the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" described below mean that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic expressions of the above terms do not necessarily refer to the same embodiment or example. Moreover, the technical features involved in the various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0039] Example 1
[0040] First, 2.5851g lithium carbonate, 6.0349g manganese carbonate, 2.5176g ferrous oxalate, 8.0521g ammonium dihydrogen phosphate, and 18mL ethanol were added to the ball mill respectively, and the mixture was ball milled for 5h to mix evenly. Then the mixture was placed in a tubular furnace and pre-sintered at 600℃ for 4h to obtain a sintered precursor of lithium manganese iron phosphate. Then the lithium manganese iron phosphate precursor and 0.9595g of 3-aminopropyltriethoxysilane were added to a ball mill filled with 15mL deionized water and ball milled for 4h to mix evenly. Then 1.9189g sucrose was added to the ball mill and ball milled for 4h to mix evenly. Finally, the mixture was placed in a tubular furnace, sintered at 700℃ for 10h, and the modified lithium manganese iron phosphate material was obtained after grinding and screening. The molar ratio of manganese to iron is 0.75:0.25.
[0041] Example 2
[0042] First, 2.5851g lithium carbonate, 4.0232g manganese carbonate, 5.0352g ferrous oxalate, 8.0521g ammonium dihydrogen phosphate, and 18mL ethanol were added to the ball mill respectively, and the mixture was ball milled for 5h to mix evenly. Then the mixture was placed in a tubular furnace and pre-sintered at 500℃ for 6h to obtain a sintered precursor of lithium manganese iron phosphate. Then the lithium manganese iron phosphate precursor and 0.9848g of 3-aminopropyltriethoxysilane were added to a ball mill filled with 15mL deionized water and ball milled for 4h to mix evenly. Then 1.9189g sucrose was added to the ball mill and ball milled for 4h to mix evenly. Finally, the mixture was placed in a tubular furnace, sintered at 650℃ for 12h, and the modified lithium manganese iron phosphate material was obtained after grinding and screening. The molar ratio of manganese to iron is 0.5:0.5.
[0043] Example 3
[0044] First, 2.5851g lithium carbonate, 6.0349g manganese carbonate, 2.5176g ferrous oxalate, 8.0521g ammonium dihydrogen phosphate, and 18mL ethanol were added to the ball mill respectively, and the mixture was ball milled for 5h to mix evenly. Then the mixture was placed in a tubular furnace and pre-sintered at 600℃ for 4h to obtain a sintered precursor of lithium manganese iron phosphate. Then the lithium manganese iron phosphate precursor and 0.9595g of 4-aminobutyltriethoxysilane were added to a ball mill filled with 15mL deionized water and ball milled for 4h to mix evenly. Then 1.9189g sucrose was added to the ball mill and ball milled for 4h to mix evenly. Finally, the mixture was placed in a tubular furnace, sintered at 700℃ for 10h, and the modified lithium manganese iron phosphate material was obtained after grinding and screening. The molar ratio of manganese to iron is 0.75:0.25.
[0045] Comparative Example 1
[0046] First, add 2.5851g lithium carbonate, 6.0349g manganese carbonate, 2.5176g ferrous oxalate, 8.0521g ammonium dihydrogen phosphate, and 18mL ethanol to the ball mill, and mix them evenly by ball milling for 5h. Then put the mixture into a tube furnace and pre-sinter at 600℃ for 4h to obtain a sintered precursor of lithium iron manganese phosphate. Then add the lithium iron manganese phosphate precursor to a ball mill containing 15mL deionized water and mix them evenly by ball milling for 4h. Then add 2.6865g sucrose to the ball mill and mix them evenly by ball milling for 4h. Finally, put the mixture into a tube furnace, sinter at 700℃ for 10h, and obtain the lithium iron manganese phosphate material after grinding and screening. The molar ratio of manganese to iron is 0.75:0.25.
[0047] Comparative Example 2
[0048] First, add 2.5851g lithium carbonate, 6.0349g manganese carbonate, 2.5176g ferrous oxalate, 8.0521g ammonium dihydrogen phosphate, and 18mL ethanol to the ball mill, and mix them evenly by ball milling for 5h. Then put the mixture into a tubular furnace and pre-sinter it at 600℃ for 4h to obtain a sintered precursor of lithium iron manganese phosphate. Then add the lithium iron manganese phosphate precursor to a ball mill containing 15mL deionized water and mix it evenly by ball milling for 4h. Finally, put the mixture into a tubular furnace, sinter it at 700℃ for 10h, and obtain the lithium iron manganese phosphate material after grinding and screening. The molar ratio of manganese to iron is 0.75:0.25.
[0049] Effect Example
[0050] First, the lithium manganese iron phosphate materials obtained in Examples 1-3 and Comparative Examples 1-2 were characterized by X-ray diffraction (XRD). Figure 3As shown, it can be found that the characteristic peaks of the materials of Example 1-3 with the addition of silane coupling agent are consistent with the characteristic peaks of Comparative Example 1-2, and no impurity phase appears, indicating that the addition of silane coupling agent, the change of manganese iron lithium ratio and the sintering parameters will not affect the olivine structure of lithium manganese iron phosphate.
[0051] The synthesized material was then tested by scanning electron microscopy (SEM) to observe the crystal size and morphology. Figure 4 As shown, the particle size of the lithium iron manganese phosphate material particles in Examples 1-3 and Comparative Example 1 is all 1-1.5 μm, and all are spherical, indicating that the addition of silane coupling agent will not have a significant effect on the size and morphology of the lithium iron manganese phosphate crystals. Comparative Example 2 does not add sucrose to carbon-coat the material, resulting in a larger crystal size with a particle size distribution of 2-3 μm.
[0052] Subsequently, lithium manganese iron phosphate material, SP carbon black and PVDF were added to NMP in a mass ratio of 8:1:1. The slurry was then ball-milled to a suitable viscosity and fineness, and evenly coated on aluminum foil, and placed in an oven for vacuum drying to obtain a positive electrode. Finally, the positive electrode, metal lithium negative electrode, diaphragm and electrolyte were assembled into a button battery for electrochemical performance testing. The discharge specific capacity results at different rates are shown in Table 1.
[0053] Table 1 Specific capacity of embodiment 1-3 and comparative example 1-2
[0054] 0.2C specific capacity (mAh / g) 1C specific capacity (mAh / g) Example 1 154.9 139.3 Example 2 152.1 136.4 Example 3 153.4 138.3 Comparative Example 1 144.1 130.8 Comparative Example 2 110.2 87.5
[0055] As can be seen from Table 1, after adding the silane coupling agent, the specific capacities of Examples 1-3 are significantly better than those of Comparative Examples 1-2. Since no sucrose is added to Comparative Example 2, its conductivity is worse than that of Comparative Example 1, and its specific capacity is lower. The 0.2C charge-discharge curves of Example 1 and Comparative Example 1 are shown in FIG. Figure 5 As shown, it can be seen that the specific capacity difference between the two is significant. The above results show that adding silane coupling agent can effectively improve the uniformity and integrity of carbon coating and improve Li + The diffusion rate of lithium manganese iron phosphate is improved. Figure 6 It can be seen from the rate performance test that the discharge specific capacity of the material in Example 1 at different rates is better than that of the material in Comparative Example 1, showing a more excellent rate performance. Finally, we compared the cycle performance of the two groups of materials in Example 1 and Comparative Example 1 at 0.2C. The test results are as follows: Figure 7 As shown, it can be seen that the cycle performance of the two groups of materials is not much different in the first 40 weeks. After 40 weeks, the capacity retention rate of comparative example 1 suddenly dropped to 94% and continued to decline, and that of example 1 slightly dropped to 98%, indicating that the silane coupling agent coating layer can effectively improve the cycle performance of the positive electrode material.
[0056] It will be easily understood by those skilled in the art that the above descriptions are merely embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium manganese iron phosphate positive electrode material, characterized in that: The preparation method of the lithium manganese iron phosphate positive electrode material comprises the following steps: (1) adding a lithium source, an iron source, a manganese source, and a phosphorus source into a ball mill containing ethanol and mixing by ball milling to obtain a mixture; (2) drying the mixture obtained by mixing in step (1), placing it in a tube furnace, and calcining it in an inert atmosphere to obtain a lithium manganese iron phosphate sintered precursor; (3) adding the lithium manganese iron phosphate sintering precursor and the silane coupling agent into a ball mill filled with deionized water and mixing them by ball milling; (4) adding sucrose to the mixture obtained by mixing in step (3), and mixing by ball milling; (5) drying the mixture obtained by mixing in step (4), placing it in a tube furnace, calcining it in an inert atmosphere, and finally screening it to obtain a modified lithium manganese iron phosphate positive electrode material; The silane coupling agent is selected from one or more of 3-aminopropyltriethoxysilane, 4-aminobutyltriethoxysilane, and 3-aminopropyltrimethoxysilane.
2. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (1), the lithium iron manganese phosphate material LiFe x Mn 1-x The molar ratio of PO4 is put into the lithium source, iron source, manganese source and phosphorus source, wherein the molar ratio of Mn / Fe element = 1-x / x, 0.1≤x≤0.
8.
3. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The ball milling time in step (1) is 4-8 hours.
4. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: In the step (2), the calcination temperature is set at 500-650°C.
5. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The calcination time in step (2) is set at 2-10 hours.
6. The method for preparing the lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The added amount of the silane coupling agent is 1-10 wt %.
7. The method for preparing lithium iron manganese phosphate positive electrode material according to claim 1, characterized in that: The ball milling time in step (3) is 2-6 hours.
8. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The ball milling time in step (4) is 2-6 hours.
9. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The amount of sucrose added in step (4) is 5-20 wt%.
10. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: In the step (5), the calcination temperature is set at 650-800°C.
11. The method for preparing lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The calcination time in step (5) is set at 4-14 hours.
Citation Information
Patent Citations
Lithium ion battery anode material manganese lithium iron phosphate and preparation method thereof
CN103956491A
Carbon-lithium iron phosphate multi-phase and single-layer co-coated lithium ferric manganese phosphate material and preparation method thereof
CN105185992A